Polymersomes Prepared from Thermoresponsive Fluorescent Protein-Polymer Bioconjugates: Capture of and Report on Drug and Protein Payloads - Wong, Chin Ken; Laos, Alistair J.; Soeriyadi, Alexander H.; Wiedenmann, Jörg; Curmi, Paul M. G.; Gooding, J. Justin; Marquis, Christopher P.; Stenzel, Martina H.; Thordarson, Pall (Angewandte Chemie International Edition, 2015)
Polymersomes provide a good platform for targeted drug delivery and the creation of complex (bio)catalytically active systems for research in synthetic biology. To realize these applications requires both spatial control over the encapsulation components in these polymersomes and a means to report where the components are in the polymersomes. To address these twin challenges, we synthesized the protein–polymer bioconjugate PNIPAM‐b‐amilFP497 composed of thermoresponsive poly(N‐isopropylacrylamide) (PNIPAM) and a green‐fluorescent protein variant (amilFP497). Above 37 °C, this bioconjugate forms polymersomes that can (co‐)encapsulate the fluorescent drug doxorubicin and the fluorescent light‐harvesting protein phycoerythrin 545 (PE545). Using fluorescence lifetime imaging microscopy and Förster resonance energy transfer (FLIM‐FRET), we can distinguish the co‐encapsulated PE545 protein inside the polymersome membrane while doxorubicin is found both in the polymersome core and membrane. Temperature‐induced self‐assembly: A temperature‐sensitive green fluorescent (amilFP497) protein–polymer bioconjugate forms polymersomes above 37 °C which encapsulate a mixture of pink fluorescent protein (PE545) and a red drug molecule (DOX). The spatial location of the payload is revealed by fluorescence lifetime microscopy.